Management and outcomes of caesarean scar pregnancy in medina maternity and children hospital - Salama, Bahaa Eldin; Mufti, Mohammed; Alruwathi, Rehab; Yassin, Tarig; Tuker, Roqayah; Nasser, Hamza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Undergoing previous cesarean section (CS) can have the possibility for implantation of embryonic sac of any later gestation throughout its scar evolving what was known as a scar pregnancy (SP). The aim of this study to describe the diagnosis, treatment and outcomes of caesarean SP in Medina maternity and children hospital. This a case series study encompassed all patient diagnosed and managed as cesarean SP in Medina maternity and children hospital, Medina (MMCH), Saudi Arabia in the period from January 2020 to January 2021. Demographics, clinical and discharge data were attained from the previous hospital electronic records, nursing notes, anesthesia sheets, operative notes, discharge papers, and outpatient clinic documents. A total of 11 women detected by ultrasound (US) and magnetic resonance imaging (MRI) as SP. The mean age of women was 36±3.8 years. The median number of repeated CS was 2 while the mean gestational age was 50.6±7.8 days. The interval from diagnosis to management ranged from 2 to 9 days with a median of 4 days, and the interval between start treatment and negative Beta human chorionic gonadotropin β-hCG ranged from 21 to 135 days with a median of 62 days. The mean interval from last CS until this pregnancy is 39.7±19.2 months. Systemic methotrexate (MTX) given in a single dose for two patients while nine patients received multiple doses. Local MTX given for six cases. Bleeding as a complication occurred with two out of the eleven patients. MTX was actual treatment for SP, but bigger multicenter randomized-controlled trials involving more cases are essential to validate our conclusions.